New Advances in Bioelectrochemical Systems in the Degradation of Polycyclic Aromatic Hydrocarbons: Source, Degradation Pathway, and Microbial Community - Yimeng Feng; Xuya Zhu; Xiulin Huang; Fengxiang Li (Energies)
Because of their high persistence, polycyclic aromatic hydrocarbons (PAHs) are found in a wide range of settings and pose a health risk to both humans and other organisms. Degradation of PAHs is an essential part of environmental management. By combining biological metabolism and electrochemical processes, bioelectrochemical systems (BESs) can degrade PAHs and provide important applications by converting the chemical energy of pollutants into electrical energy for energy conversion and recovery. This review provides a comprehensive introduction to PAH degradation by BESs, including PAH sources, degradation effects of BESs, performance enhancement methods, degradation pathways, and dominant microorganisms. By focusing on the relevant research in recent years, the main innovative research focuses on the optimization of the configuration, the electrode preparation, and the media additions to improve the removal performance of PAHs. It demonstrates the potential of BESs in the field of environmental remediation, especially their effectiveness in treating difficult-to-degrade pollutants such as PAHs, by concentrating on the application and mechanism of BESs in PAH degradation. This review is intended to provide the inexperienced reader with an insight into this research area and to point out directions for future research, especially in the design optimization of BESs and microbial community analysis.